Stunting Consultation by the Collaborative KKN Team as a Participatory Strategy to Overcome Stunting Early Childhood in Tanjungsari Village - Masud Hermansyah; Dea Ananda Raharjo; Della Utami Inayaturrahman; Elisa Wardatul Awaliya; Maulida Adelia Putri (Medikun Publisher, 2024)
Stunting Consultation is an initiative of the Collaborative KKN Team that aims to overcome stunting in early childhood in Tanjungsari Village, Umbulsari District. This activity is carried out with a participatory approach involving various parties, including village communities, health workers, and village officials. During program implementation, comprehensive data regarding stunting in Tanjungsari Village was successfully collected, revealing the existence of families at significant risk of stunting. Through Forum Group Discussions (FGD) and participatory meetings, public awareness of the stunting problem increased, and active collaboration between various parties was key in formulating concrete recommendations to tackle stunting effectively. The results reflect the importance of a participatory approach in overcoming the stunting problem, with the hope that these steps will bring significant positive changes in the welfare of young children in Tanjungsari Village